The Effect Analysis of Solvency Ratio, Profitability Ratio and Inflation on Stock Return - Olivia The; Dea Afifah Wijaya; Hery Harjono Muljo (Bina Nusantara University, 2022)
The emergence of COVID-19 in 2019 spread across many countries and had a huge impact on the economy. When the information on the first COVID-19 patients was announced, it had a direct impact on the decline in stock prices and stock return. Solvency ratio, profitability ratio and inflation have a relationship and influence the stock return. The ratios used are Debt to Equity Ratio (DER), Return on Equity (ROE), Price to Earnings Ratio (PER), Dividend Payout Ratio (DPR). The secondary data of this study is in the form of company financial statements that have been published from the period of 2017 to 2020. Researchers used the coefficient of determination test, t test and F test (Anova). The result of this study indicates that Debt to Equity Ratio (DER) and Inflation have a positive effect on stock return, while Return on Equity (ROE), Price to Earnings Ratio (PER), and Dividend Payout Ratio (DPR) have no effect on stock return.